Gender-Sensitive Parliament Approach in Local Regulations Enactment: A Case Study of Tangerang Regency, Indonesia - Nurdin Nurdin; Abdul Aziz SR (Dealings Foundation Institute, 2026)
This research aims to analyze the gender-sensitive parliamentary approach in the formation of gender-sensitive local regulations that impact gender equality in sustainable development achievement in Tangerang Regency, Indonesia. The data collection methods are through literature studies, documentation, observation, and the results of focus group discussions. The results of the study show that a gender-sensitive approach to the role of the local parliament has succeeded in increasing the percentage of the gender equality index, such as the human development index, gender development index, gender empowerment index, and gender inequality index. While the achievement of the sustainable social development index increased significantly, which can be analyzed from the labor force participation rate, open unemployment rate, and poverty rate after gender-sensitive regional regulations were implemented from 2022 to 2023. These achievements have an impact on the quality of life and welfare of the community. The conclusion of this research explains that the stagnation of progress on gender equality in sustainable development can be collaborated between the Regent and the Local Parliament in order to increase collective gender awareness in fighting for women's interests in local development. This research contributes to enriching concepts, theories, and references related to gender-sensitive parliaments that can explain cases of gender equality and gender development policies in local politics.